Structural Investigation of Hybrid Peptide Foldamers Composed of α‐Dipeptide Equivalent β‐Oxy‐δ5‐amino Acids. Issue 19 (9th March 2020) - Reja, Rahi M.; Kumar, Vivek; George, Gijo; Patel, Rajat; Puneeth Kumar, DRGKoppalu R.; Raghothama, Srinivasarao; Gopi, Hosahudya N.
Abstract: Due to their equivalent lengths, δ‐amino acids can serve as surrogates of α‐dipeptides. However, δ‐amino acids with proteinogenic side chains have not been well studied because of synthetic difficulties and because of their insolubility in organic solvents. Recently we reported the spontaneous supramolecular gelation of δ‐peptides composed of β(O)‐δ 5 ‐amino acids. Here, we report the incorporation of β(O)‐δ 5 ‐amino acids as guests into the host α‐helix, α, γ‐hybrid peptide 12‐helix and their single‐crystal conformations. In addition, we studied the solution conformations of hybrid peptides composed of 1:1 alternating α and β(O)‐δ 5 ‐amino acids. In contrast to the control α‐helix structures, the crystal structure of peptides with β(O)‐δ 5 ‐amino acids exhibit α‐helical conformations consisting of both 13‐ and 10‐membered H‐bonds. The α, δ‐hybrid peptide adopted mixed 13/11‐helix conformation in solution with alternating H‐bond directionality. Crystal‐structure analysis revealed that the α, γ 4 ‐hybrid peptide accommodated the guest β(O)‐δ 5 ‐amino acid without significant deviation to the overall helix folding. The results reported here emphasize that β(O)‐δ 5 ‐amino acids with proteinogenic side chains can be accommodated into regular α‐helix or 12‐helix as guests without much deviation of the overall helix folding of the peptides. Abstract : Peptide mimics : Conformational properties of peptides composed of new β‐oxy‐δ‐amino acids are studied as dipeptide surrogates both in solution and as single crystals. Structural analysis suggests that the β‐oxy‐δ‐amino acids can be accommodated into helices without significant deviation in the overall helical folding (see figure).